An Investigation on Influential Factors on Students’ Perceived Employability in Higher Education, Guangzhou, China - Yan, Yan (Scholar: Human Sciences, 2025)
Purpose: This study aims to explore the impacting factors of the perceived employability of graduates from a vocational college in Guangzhou, China. Research design, data, and methodology: The researchers designed a 12-week IDI intervention plan. Firstly, interviews were conducted with graduates before the IDI stage, and the required qualitative data and quantitative data from 30 graduates were collected through a questionnaire. Then, using a questionnaire that has undergone reliability and validity testing to distribute the questionnaire to 517 vocational college graduates. Finally, design and implement an IDI intervention plan to compare the changes in the levels of each variable between Pre-IDI and Post-IDI through paired sample t-tests. Results: Multiple linear regression analysis shows that career self-management, proactive personality, self-efficacy, and core self-evaluation have a significant impact on the perceived employability of vocational college graduates, while protean career orientations have no significant impact on the perceived employability of vocational college graduates. The results of the paired sample t-test showed significant differences in career self-management, proactive personality, self-efficacy, core self-evaluation, and perceived employability levels among vocational college graduates between pre-IDI and post-IDI. Conclusions: The IDI intervention program used in this study effectively improved career self-management, proactive personality, self-efficacy, core self-evaluation, and perceived employability levels of vocational college graduates.